ЖИЫНТЫҚ (КОНСОЛИДАРЛЫ) ҚАДАҒАЛАУ – БҰЛ ҚАРЖЫНЫҢ АЙҚЫНДЫЛЫҒЫ (Journal of actual problems of jurisprudence, 2019)
Given article is devoted the consolidated supervision as one of types of bank supervision. In article is shown experiment offoreign countries in the consolidated supervision of bank activity and to be told about system of work of the consolidatedsupervision.